2021
DOI: 10.3390/microorganisms9081585
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing Refines Knowledge on the Population Structure of Mycobacterium bovis from a Multi-Host Tuberculosis System

Abstract: Classical molecular analyses of Mycobacterium bovis based on spoligotyping and Variable Number Tandem Repeat (MIRU-VNTR) brought the first insights into the epidemiology of animal tuberculosis (TB) in Portugal, showing high genotypic diversity of circulating strains that mostly cluster within the European 2 clonal complex. Previous surveillance provided valuable information on the prevalence and spatial occurrence of TB and highlighted prevalent genotypes in areas where livestock and wild ungulates are sympatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 53 publications
4
43
0
Order By: Relevance
“…Despite the small sample size included in this study, this picture is in agreement with findings of previous studies in Spain and elsewhere on the potential effect of local risk factors (i.e., spatial proximity, extensive management in beef herds, contact with other sources of infection) in bTB endemic areas (Green et al, 2008;Biek et al, 2012;Pozo et al, 2020). Additionally, our results are in agreement with a previous study conducted in Portugal, where the observed genetic diversity supported the natural circulation of M. bovis for a long time with multiple interactions of different host species (Reis et al, 2021). Interaction with wildlife reservoirs was identified as the second most important cause of herd breakdowns in Spain, after residual infection (Guta et al, 2014a).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite the small sample size included in this study, this picture is in agreement with findings of previous studies in Spain and elsewhere on the potential effect of local risk factors (i.e., spatial proximity, extensive management in beef herds, contact with other sources of infection) in bTB endemic areas (Green et al, 2008;Biek et al, 2012;Pozo et al, 2020). Additionally, our results are in agreement with a previous study conducted in Portugal, where the observed genetic diversity supported the natural circulation of M. bovis for a long time with multiple interactions of different host species (Reis et al, 2021). Interaction with wildlife reservoirs was identified as the second most important cause of herd breakdowns in Spain, after residual infection (Guta et al, 2014a).…”
Section: Discussionsupporting
confidence: 93%
“…These ambiguous calls occurred in non-informative SNPs (SNPs shared by all the isolates included in the study that were not relevant to define the clustering pattern presented here). Erroneous calls were meticulously verified with IGV, and reliable SNPs were manually corrected as suggested by the vSNP documentation ( Orloski et al, 2018 ) and performed in several studies ( Orloski et al, 2018 ; Salvador et al, 2019 ; Perea et al, 2021 ; Reis et al, 2021 ). In case erroneous calls fell in areas with low coverage or mapping issues these were manually filtered out.…”
Section: Discussionmentioning
confidence: 99%
“…This category with a determined function is the most frequent in our analysis. Genes encoding replication, recombination, and DNA repair functions seem to play an important role in the evolution of highly clonal bacteria such as M. bovis ( Vultos et al, 2008 ; Mestre et al, 2011 ; Reis et al, 2021 ). Other frequent categories are “Intracellular trafficking, secretion, and vesicular transport” (7%, 26/369), “Cell wall/membrane/envelope biogenesis” (6%, 22/369), and “Transcription” (6%, 22/369) or “Cell motility” (5%, 20/369).…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterium bovis isolates dataset. Forty-two newly sequenced M. bovis genomes from an endemic multi-host TB scenario in Portugal (details below), previously characterized from an epidemiological point of view 36 , were at the centre of this work. Considering that the dataset from Portugal only has representatives of European 2 clonal complex and strains without complex assigned, publicly available whole genome sequencing data was added in order to enlarge the dataset with representatives from all M. bovis clonal complexes.…”
Section: Methodsmentioning
confidence: 99%